Dinamika Perkembangan Pariwisata Pusaka: Tinjauan dari Sisi Penawaran dan Permintaan di Kota Bandung - Patria, Teguh Amor (Bina Nusantara University, 2015)
Tourism is one of the largest industries in the world today, and heritage tourism is one tourism segment that has shown a rapid growth. Heritage tourism in Indonesia only began to grow in the beginning of this millennium, marked by emergence of heritage tourism organizations in a number of major cities. In the city of Bandung, heritage tourism activities were initially organized in 2003 following the birth of Bandung Trails. The organization has been active in organizing heritage tours annually. Identification of heritage tourism development, both from demand and supply side, is the goal of a research that became the basis for this paper. The type of the research is qualitatiive and the population taken was the participants of tours organized by the Bandung Trails between 2003 and 2007. Samples were chosen randomly involving around 750 respondents who were given questionnaires from which primary data of profiles and demand patterns were generated. Aside from that, secondary data from literatures were used to identify the conditions of heritage tourism products at the supply side. Heritage tourism is a new phenomenon in Bandung that began to develop in the early millennium and pioneered by grassroots communities in heritage conservation. Findings of this research include, from the supply side, some challenges in the development of heritage tourism in Bandung, such as weak law enforcement, limited economic condition of local communities, and lack of attachment between the communities and heritage objects. From the demand side, heritage tourists in Bandung was domnated by young people aged 19-30 (78%) and it is assumed that there is a connection between level of education and interest in heritage tourism.